DEVELOPMENT AND VALIDATION OF RP-HPLC METHOD FOR SIMULTANEOUS ESTIMATION OF CHLORPHENIRAMINE MALEATE AND DIETHYLCARBAMAZINE CITRATE IN PHARMACEUTICAL DOSAGE FORMS - Daravath, Bhaskar; Santhosh Reddy, Gouru; SK, Kamarapu (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The present study describes method development and subsequent validation of RP-HPLC method for the simultaneous estimation of Diethylcarbamazine citrate and Chlorpheniramine maleate in tablet dosage forms. Method: Reversed-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated for simultaneous estimation of Diethylcarbamazine citrate and Chlorpheniramine maleate in combined dosage forms. RP-HPLC separation was achieved by using Kromasil C18 column (250mm 4.6mm, 5mm) with mobile phase consisting of (80:20) Acetonitrile: Potassium di hydrogen phosphate solution (0.01M, pH 3.0 adjusting with Ortho phosphoric acid) with a flow rate 1.0 ml/min (UV detection 238nm). Results: The retention time of Diethylcarbamazine citrate and Chlorpheniramine maleate were found to be 2.808 min and 4.042 min respectively. The developed method was validated as per ICH guidelines using the parameters such as accuracy, precision, linearity, LOD, LOQ and robustness. Linearity was observed over the concentration range 10â€“50 Âµg/ml with regression equation y=1099x+1143, R2=0.999 for CPM and y=10972x+14199, R2=0.998 for DEC. Conclusion: The developed and validated RP-HPLC method was successfully used for the quantitative analysis of Diethylcarbamazine citrate and Chlorpheniramine maleate in combined tablet dosage forms. Â KEY WORDS: Diethylcarbamazine citrate, Chlorpheniramine maleate, Eofil Forte tablet dosage forms, HPLC, Method validation.